2020
DOI: 10.1002/aoc.5931
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, crystal structure and toxicity evaluation of Co (II), Cu (II), Mn (II), Ni (II), Pd (II) and Pt (II) complexes with Schiff base derived from 2‐chloro‐5‐(trifluoromethyl)aniline

Abstract: A bidentate NO donor Schiff base, 2-(((2-chloro-5-(trifluoromethyl)phenyl) imino)methyl) phenol (HL 1) and its complexes [Co(L 1) 2 (H 2 O) 2 ] (1), [Cu(L 1) 2 ] (2), [Mn(L 1) 2 (H 2 O) 2 ] (3), [Ni(L 1) 2 (H 2 O) 2 ] (4), [Pd 2 (L 1) 2 (OAc) 2 Á1.16H 2 O] (5), [Pt (L 1) 2 ] (6) were synthesized and characterized by different physico-chemical techniques including elemental and thermal analysis, magnetic susceptibility measurements, molar electric conductivity, IR, 1 H-NMR, 13 C-NMR, UV-Vis, mass spectroscopies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The 13 C‐NMR spectra (DMSO, 125 MHz, δ, ppm): δ = 165.4; 164.5—specific for the C7 atom involved in the azomethine bond, 163.2; 145.6; 134.8; 132.4; 130.9; 129.0; 123.8; 123.7; 116.8; 112.9; 107.3; 100.8; and 55.6 ppm. [ 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…The 13 C‐NMR spectra (DMSO, 125 MHz, δ, ppm): δ = 165.4; 164.5—specific for the C7 atom involved in the azomethine bond, 163.2; 145.6; 134.8; 132.4; 130.9; 129.0; 123.8; 123.7; 116.8; 112.9; 107.3; 100.8; and 55.6 ppm. [ 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…23 The peaks at 1352 and 1622 cm À1 can be assigned to C-N and N-H bending, respectively. 36,37 Notably, two new peaks at 1492 and 1327 cm À1 are detectable for the TFPAI-treated sample in comparison with the control lm, which are, respectively, corresponding to the vibrational modes of aromatic C]C and -CF 3 of TFPAI, [38][39][40] indicative of the accommodation of TFPAI in the top perovskite lm.…”
Section: Resultsmentioning
confidence: 99%
“…On comparing the activity of ligand with that of complex, it was found that the complex showed greater activity which can be explained on chelation theory after complexation biocidal properties will increase due to synergistic effect of metal ions. The metal‐chelate and complex toxicity would lead to increase the lipophilic nature of complexity 60,61 . Moreover because of their positive charge can be sharing with donor groups and delocalization of p‐electron over the system.…”
Section: Resultsmentioning
confidence: 99%
“…The metal-chelate and complex toxicity would lead to increase the lipophilic nature of complexity. 60,61 Moreover because of their positive charge can be sharing with donor groups and delocalization of p-electron over the system. Moreover the chelation may influence the polarity of metal atom.…”
Section: Microbial Activity Of the Compoundsmentioning
confidence: 99%